BFGF in the CSF and serum of sALS patients. (28th January 2015) - Gong, Z.; Gao, L.; Guo, J.; Lu, Y.; Zang, D.
<x xml:space="preserve">Abstract</x> Objectives Amyotrophic lateral sclerosis is a fatal neurodegenerative disease characterized by selective motor neuron loss in the brain and spinal cord. The cause of this selective death of motor neurons is still unclear, but among several pathomechanisms that have been discussed, the loss of neurotrophic factors is one hypothesis. Basic fibroblast growth factor 2 (bFGF) may be a potential neurotrophic factor for slowing various neurodegenerative diseases, but its potential role in the prognosis of ALS is not known. Methods To explore the role of bFGF in ALS, we investigated changes in bFGF in the CSF and serum from patients with sALS and from the control group. Furthermore, we analyzed the correlations between bFGF, disease duration, disease progression rate, ALSFRS‐r score and survival. Results The level of bFGF increased in both the CSF and serum in sALS patients. It was higher in patients with longer durations. It was negatively correlated with disease progression rates, especially in the later stages of sALS, but showed no linear correlation with ALSFRS‐r. In an analysis of the relationship between bFGF and survival, we found that sALS patients with high levels of bFGF had significantly higher cumulative survival rates than patients with low levels of bFGF. Discussion and Conclusion In conclusion, endogenous bFGF increased both in the CSF and serum of sALS patients and it may be a useful biomarker that could predict disease progression and survival.